LICCHAVI INSCRIPTIONS: A CULTURAL MONUMENT OF KATHMANDU VALLEY - Parajuli, Sandhya Khanal (International Journal of Research -GRANTHAALAYAH, 2024)
Numbers of Licchavi inscriptions installed by the Licchavi rulers are found to be established around Kathmandu valley. They are profoundly installed since 5th century CE. Inscriptions are the authentic evidence that have made possible to construct a clear apparition of Licchavi age. They are potential from historical, cultural as well as monumental point of view. Inscriptions are concrete attest of several issues concerned to their reign and a strong indicator to mend the structure of an ancient settlements. They are not only source of defining tangible and intangible inheritances of the age but valuable monument associated with several cultural practices. Despite its historical significance, traditional practices related with this monument emerged through local perception have been an essential part of Nepalese culture through the time. In this context, what are the recent eminence of Licchavi inscriptions? How are they perceived by local communities and expressed through? And how far the inscriptions have been affected by traditional activities? are the questions or problems related to these valuable monuments that have been unanswered. To answers these queries have been attempted in this paper. To reveal the facts, primary and secondary sources have been adopted. Survey of inscriptions of the valley, collection of information through interviews and observation of traditional practices were conducted with the collection of photographs. Related literatures as a secondary source were consulted. The collected facts were analyzed to draw conclusion in a descriptive manner. From these facts, it has been revealed that Licchavi inscriptions as a monumental heritage are in crisis with several threats in lack of proper conservation. As per location they stand and the structural theme they comprise, they have been perceived as purposeful object or deities rather than a historical monument by local communities and are expressed by offering of materials with great belief and devotion. The tradition to some extent has been gradually ruining the inheritances and should be taken into consideration soon.